European Wars, Civil Conflicts, and National Projects. The Neapolitan Restorations (1799-1866) Revisited | Guerras europeas, conflictos civiles, proyectos nacionales. Una interpretación de las restauraciones napolitanas (1799-1866) - Carmine Pinto (Pasado y Memoria, 2014)
Examining counter-revolution through its greater achievements, that is, the four winning restorations, and also their disastrous fall, that is, the defeated restoration, may contribute to enrich traditional perspectives on the Kingdom of the Two Sicilies’ resistance and the crisis. European conflicts, civil wars, state constructions and modern national identity shaping are phenomena which intertwine the complicated history of the Neapolitan Kingdom. It is from the perspective of the dynastic (1799 and 1815) and absolutist restorations (1821), that we may insert in a general interpretative scheme the controversy between internal conflict and international crisis, their relationship with the shaping of ideas and nationalist affiliation and, finally, their comparison with the counter-revolution in the Bourbon world. The paradigm represented by this conflict allows for a contrast with the wider French and Spanish-American Bourbon world. We may thus consider both the success of Neapolitan legitimism and its collapse in 1860, as well as the reasons for its recent recovery in the Italian collective awareness. | La elección de examinar la contrarrevolución a través de sus mayores éxitos, las cuatro restauraciones victoriosas, y su derrota, la restauración fallida, puede enriquecer las perspectivas tradicionales sobre la resistencia y la crisis del Reino de las dos Sicilias. Los conflictos europeos, las guerras civiles, las construcciones estatales y la creación de identidades nacionales modernas son fenómenos que se entrecruzan con la complicada historia del reino napolitano. A través de la perspectiva de las restauraciones, bien dinásticas (1799 y 1815), o bien absolutistas (1821 y 1849), podemos insertar en un esquema interpretativo general la dialéctica entre conflicto interno y crisis internacionales, la interrelación con la formación de las ideas y adscripciones nacionalistas y la comparación con la contrarrevolución en el mundo borbónico. El paradigma del conflicto nos permite también el contraste con el más amplio mundo borbónico, francés y, sobre todo, iberoamericano. De este modo podemos reflexionar tanto sobre el éxito del legitimismo napolitano como sobre los términos de su derrota en 1860 y sobre las razones de su reciente fortuna en el imaginario colectivo italiano.